Analysis of the impact of the quality of service to the elderly on their loyalty through a Memorable experience and satisfaction among the elderly in 5-star hotels in Mashhad. - tina ezazi; vajihe hoshyar (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to analyze the effect of the quality of service to the elderly on their loyalty through a memorable experience and satisfaction among the elderly customers of 5-star hotels in Mashhad. The research method is applicable in terms of purpose and the method of data collection is descriptive-survey. The statistical population of the research is all elderly people over 70 years of age who refer to 5-star hotels in Mashhad and have used that hotel at least 3 times, the number of which is unknown, according to the tenfold formula of the questionnaire questions, 270 samples were selected by the available non-random method. The data was collected through a standard questionnaire and then analyzed by structural equation modeling using Smart pls 2 and SPSS 24 softwares. The findings show that the electronic customer relationship management variable had a positive and significant impact on product innovation development and the product innovation development variable had a positive and significant impact on marketing performance. Also, customer knowledge had a positive and significant impact on both marketing performance and product innovation development, and electronic customer relationship management and customer knowledge through product innovation development had a positive and significant impact on marketing performance. Extended Abstract Introduction Having loyal customers in intense competition is a key factor for the success of organizations, therefore, the plans and strategies of organizations move towards the factors influencing customer loyalty, and obtaining customer satisfaction is an effective step to achieve this important goal (Fallah & Hamidi, 2021). Customer satisfaction is achieved when customers have a memorable and enjoyable experience of receiving services and products (Agarwal, Ira. Gowda, 2020). With the intensification of competition, companies have realized that providing a memorable experience to customers is very important to survive and gain a competitive advantage (Roozen & Katidis, 2019). Obviously, companies should focus on creating positive experiences to win the minds of customers (Micu, 2019); therefore, creating memorable experiences is important to retain old customers and attract new ones (Chen & Wu, 2022). However, the important factor in the formation of a valuable customer experience, followed by customer satisfaction; which enables the realization of customer loyalty, is the quality of service. Service quality is the ability of a product to meet the desired goal with the minimum possible cost (Bui et al., 2022). In the hotel industry, service quality is inevitable in order for the hotel to be distinguished from their competitors and to satisfy customers (Feng et al., 2018). In the meantime, the increase in the age of people and the expansion of the circle of elderly people in the society have led managers and hotel owners to plan and pay attention to providing quality services according to the wishes of the elderly (Prentice et al., 2022). Because increasing the satisfaction and loyalty of people of different ages requires knowing more about the different demands and needs of customers during their experience in the hotel. The organization can create value from providing its services and products when the service and product are provided according to the opinion and taste of the customers, which shows the intelligence of the managers in paying comprehensive attention to the customers (Mansouri et al., 2022). Therefore, improving service quality has become an important tool in the hotel industry in order to achieve a competitive advantage and retain customers. Satisfied hotel customers are more likely to return than dissatisfied ones (Liu, 2023). Currently, most organizations have realized that customer satisfaction can lead to their long-term success; the tourism industry, especially hotels, is no exception to this rule (Kim & Han, 2023). The best hotels consider customer satisfaction as the most important competitive weapon to achieve profit (Dah et al., 2023). According to the above explanations, the main question in the current research is whether the quality of service to the elderly through a memorable experience and satisfaction among the elderly customers of 5-star hotels in Mashhad leads to the loyalty of the elderly or not. Theoretical Literature Rachman et al., (2023) in a research entitled "Evaluation of the effect of service quality and product quality on customer satisfaction with the store" reached these results that service quality has a positive and significant effect on customer satisfaction. Prentice et al., (2022) conducted a research entitled "Investigating the role of memorable experience and emotional intelligence in the loyalty of senior customers to hotels for the elderly". The findings showed that service quality has a significantly greater impact on customer satisfaction, memorable experience, and customer loyalty. In addition, memorable customer experiences mediate the relationship between service quality and organizational outcomes. kiani et al., (2022) conducted a study entitled "Investigation of aesthetic factors and service quality on the perceived value, loyalty and satisfaction of customers of swimming pools in Kermanshah province". The results showed that there is a positive and significant effect between service quality and customer loyalty and performance. Research Methodology This research is applicable in terms of purpose and descriptive-survey in terms of nature. In terms of data collection, it is a field research using a questionnaire tool and based on structural equation modeling. The statistical population of the research is all seniors over 70 years of age who refer to 5-star hotels in Mashhad and have used that hotel at least 3 times, in uncertain volume. Based on the tenfold formula of questionnaire questions, 270 samples were selected in a non-random method. The data collection tool was a questionnaire, which was distributed after determining its validity and reliability. The questionnaire included 27 questions related to the main research variables, which were tested for reliability and validity after preliminary distribution. To check the reliability of the questionnaire, Cronbach's alpha method and composite reliability were used and confirmed. To check its validity, face validity and factor validity (through confirmatory factor analysis) were used. The third version of SmartPLS software was used for data analysis. Research Findings In order to check and test the hypotheses or the conceptual model of the research, smart pls 3 software was used, and the results showed that the effect of the quality of service to the elderly on the memorable experience was calculated to be equal to (0.42), which indicates a favorable effect. The t-statistic of the test was also obtained (8.60), which is greater than the critical value of t at the 5% error level, i.e. (1.96), and shows that the effect is significant. The effect of the quality of service to the elderly on customer satisfaction has been calculated to be equal to (0.27), which indicates a favorable effect. The t-statistic of the test was also obtained (3.38), which is greater than the critical value of t at the 5% error level, i.e. (1.96), and it shows that the effect is significant. The impact of memorable experience on customer loyalty has been calculated equal to (0.28), which indicates a favorable impact. The t-statistic of the test was also obtained (3.64), which is greater than the critical value of t at the 5% error level, i.e. (1.96) and shows that the effect is significant. The effect of customer satisfaction on customer loyalty has been calculated as (0.26), which indicates a favorable effect. The t-statistic of the test was also obtained (2.86), which is greater than the critical value of t at the 5% error level, i.e. (1.96), and shows that the effect is significant. The impact of memorable experience on customer satisfaction has been calculated equal to (0.48), which indicates a favorable impact. The t-statistic of the test was also obtained (6.45), which is greater than the critical value of t at the 5% error level, i.e. (1.96), and it shows that the effect is significant. The impact of service quality through memorable experience on customer loyalty has been calculated equal to (0.12), which indicates a favorable impact. The effect of service quality through customer satisfaction on customer loyalty has been calculated equal to (0.07), which indicates a favorable effect. The mediator's role is confirmed in recent hypotheses.